PENGEMBANGAN MEDIA PUZZLE AYAT UNTUK MENINGKATKAN RETENSI MEMORI JANGKA PANJANG SURAH AL-‘ALAQ AYAT 1–19 PADA SISWA MTS - Suwito, Anggi; Idi Nur , M. Zhunai; Satyrio; Surawan (Jurnal Kependidikan Media, 2026)
The purpose of this research and development (R&D) project is to create a Verse Puzzle-based learning tool that will help seventh-grade students at MTSN 1 Palangka Raya better memorize Surah Al-'Alaq verses 1-19. This innovation is based on the discovery that traditional memorization techniques, such as listening and repetition, are often boring and ineffective, especially when considering the characteristics of seventh-grade students who require a lot of visual and kinesthetic stimulation. To ensure that the final product is methodical and measurable, this study uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The Verse Puzzle product uses color differentiation for two sets of verses (1-5 and 6-19) and is made of 310 gsm Art Paper cut per phrase or word. The trial results show that this media is very suitable for use: the practicality test on seventh grade students resulted in an average percentage of positive responses of 94.25% (Very Practical category), while the validity test conducted by material and media experts resulted in an average percentage of suitability of 90.50% (Very Valid category). The Verse Puzzle Media successfully transformed memorization from a passive process into a dynamic and interesting educational process by involving students in an active remembering process through visual and kinesthetic (composing verse fragments).   Keywords: Verse Puzzle Learning Media, Memorizing Surah Al-'Alaq Verses 1–19